Factors associated with health-seeking behaviour among informal sector workers in the Kumasi metropolis of Ghana - Dina Adei; Anthony Acquah Mensah; Williams Agyemang-Duah; Lewis Aboagye-Gyasi (Cogent Public Health, 2022)
Even though studies have established that informal sector workers are prone to occupational-related diseases, not much is known about their health-seeking behaviour. This study aims to examine drivers of health-seeking behaviour among informal sector workers in the Kumasi metropolis of Ghana. A cross-sectional survey was conducted. Simple random sampling technique was used to select 350 informal sector workers. Questionnaires were used to collect the data. The study revealed that 33.5% of the participants practiced good health-seeking behaviour when they developed occupational-related diseases in 2016. The study further revealed that informal sector workers with five or more dependents (AOR: 8.482; CI: 1.265–56.872; p = 0.028) and those who spent more than an hour at a health facility (AOR: 24.040; CI: 8.508–67.927; p < 0.0001) were more probable to exhibit good health-seeking behaviour. Informal sector workers without active National Health Insurance Scheme [NHIS] (AOR: 0.149; CI: 0.052–0.430; p < 0.0001) and employees were less likely to adopt good health-seeking behaviour. Given the limited formal healthcare system and resources available, socio-demographic factors should be taken into consideration when formulating policies to encourage informal sector workers to adopt good health-seeking behaviour.